2021
DOI: 10.3390/ijerph18157887
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Willingness of Palliative Care Utilization among the Older Population with Active Cancers: A Case Study in Mandalay, Myanmar

Abstract: Palliative care is an effective, multidisciplinary healthcare service to alleviate severe illness patients from physical, psychological, and spiritual pain. However, global palliative care has been underutilized, especially in developing countries. This cross-sectional survey aimed to examine the factors associated with older cancer patients’ willingness to utilize palliative care services in Myanmar. The final sample was composed of 141 older adults, 50-years of age and above who suffered from cancers at any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“… 17 A study in Myanmar found that patients are often open to the receipt of palliative care if conducted in conjunction with their appropriate spiritual and religious traditions. 18 Possibly linked with the role of traditional belief systems in medicine is the use of complementary and alternative medicine in the region. 17 Although decisions to pursue complementary and alternative medicine for cancer may stem from cultural and religious preferences, inequitable access to care, disparate health literacy, and devastating costs of care may all similarly contribute, leading to delayed diagnosis and up-staging of tumors.…”
Section: Intersecting Disparitiesmentioning
confidence: 99%
“… 17 A study in Myanmar found that patients are often open to the receipt of palliative care if conducted in conjunction with their appropriate spiritual and religious traditions. 18 Possibly linked with the role of traditional belief systems in medicine is the use of complementary and alternative medicine in the region. 17 Although decisions to pursue complementary and alternative medicine for cancer may stem from cultural and religious preferences, inequitable access to care, disparate health literacy, and devastating costs of care may all similarly contribute, leading to delayed diagnosis and up-staging of tumors.…”
Section: Intersecting Disparitiesmentioning
confidence: 99%